Value assessment of Zamość from the perspective of 25 years on UNESCO World Heritage List - Jurczyk, Joanna; Szmygin, Bogusław (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
The historical center of Zamość was added to the UNESCO World Heritage List in 1992 and over next 25 years the city has undergone great changes. Thanks to numerous restoration, preservation and maintenance works we are now able to admire the beauty of its monuments and perfect spatial harmony. But this is not the end of planned work. Zamość Old Town is a historical part of a vibrant city and therefore needs to evolve constantly in order to satisfy the contemporary requirements of urban population. Concurrently, over that period of time theory of conservation and preservation of monuments and evaluation methodology of the value of goods inscribed on World Heritage List have developed significantly. Hence, the 25th anniversary is a perfect occasion for a renewed evaluation of Zamość Old Town’s value and more in-depth analysis in accordance with current methodology and state of knowledge. It enables further specification and indication of authentic and material carriers of its value which determine its further existence. At the same time, it will allow indicating the limits of possible interference. In addition to this, the outcome of this thorough analysis will be of great use in taking decisions on further actions and investments, which is particularly important with monuments so heterogeneous as a historical city center.